Improving the Eighth Grade Junior High School Students’ Listening Comprehension Achievement by Using Video and Google Jamboard - Nur Wahyuning Putri (Faculty of Education, 2025)
This research employed a classroom action research design. This research aimed to improve eighth-grade students' active participation and listening comprehension achievement at one of junior high school in Jember. Utilizing interactive whiteboard technologies to integrate, understand, and organize visually supported materials can enhance students' listening comprehension performance (Kirbas, 2018). Therefore, the researcher used video and Google Jamboard as a tool to improve students' active participation and listening comprehension during the teaching learning process.
Supervisor I Dra. Zakiyah Tasnim, MA Supervisor II Rizki Febri Andika H. S.Pd., M.Pd.
Keywords: Improving; Eighth Grade; Junior High School Students; Listening Comprehension Achievement